PEMBERDAYAAN MAHASISWA ILMU KELAUTAN UNIVERSITAS TANJUNGPURA BERSAMA MASYARAKAT DALAM KEGIATAN POROK BEACH CLEAN UP - Nurdiansyah, Syarif Irwan; Helena, Shifa (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2023)
Porok beach clean up is a voluntary effort to clean Porok Beach and marine waters so that the continuity of the marine ecosystem can continue. This activity involves students and the local community. The empowerment of Tanjungpura University marine science students together with the community in the Porok Beach Clean Up activity is to increase student and community awareness in maintaining the sustainable management of Porok beaches and waters as one of the tourist destinations on Lemukutan Island. The activity was attended by 40 students and 10 members of the public, who were actively involved in cleaning directly at the beaches and waters and continued with processing the collected waste and educational lectures by the implementing team. Based on the evaluation after the end of the activity, it showed that there was an increase in participants' awareness and enthusiasm in maintaining the cleanliness of the beaches and waters.Porok, beach clean up, ecosystem, lemukutan